Solution-focused brief counseling and ABC manipulation technique in self-control training to reduce aggressive behaviour - I Ketut Gading; Siti Aishah Hassan; Abu Yazid Abu Bakar; Kade Sathya Gita Rismawan (LPMPP Universitas Negeri Yogyakarta, 2021)
Aggressive behaviours in the society have been very alarming, including among high school students. To reduce aggressive behaviours, the main effort is to increase self-control. This study is aimed at describing the differences between the effectiveness of solution-focused brief counseling (SFBC) and Self-Control Training with the Antecedent-Behavioral-Consequence (ABC) manipulation technique to reduce students’ aggressive behavior tendencies. The study is a quasi-experimental research with a pretest-posttest control group design. The population of the study consists of 563 students. The sample selected by the simple random sampling technique amounts to 60 students. The data collection method of the study is a non-test technique. The instrument used for data collection is the Aggression Questionnaire (AQ) with 25 statement items. The data are analyzed using ANOVA test. The ANOVA test results show an F value of 348.300 with a significance value of 0.000 (Sig 0.05); so, it can be interpreted that both solution-focused brief counseling (SFBC) and the Self-Control Training with the Antecedent-Behavioral-Consequence (ABC) are effective in reducing aggressive behaviors. However, the ABC self-control training model is found to be more effective. Therefore, guidance and counseling teachers are expected to continue working on self-control training for children, through the ABC self-control training model.